2021
DOI: 10.1021/acsorginorgau.1c00016
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effects Provide Access to Tetrasubstituted Ring-Opening Olefin Metathesis of Bicyclo[4.2.0]oct-6-enes

Abstract: Herein, we report the origin of unexpected reactivity of bicyclo[4.2.0]oct-6-ene substrates containing an α,β-unsaturated amide moiety in ruthenium-catalyzed alternating ring-opening metathesis polymerization reactions. Specifically, compared with control substrates bearing an ester, alkyl ketone, nitrile, or tertiary amide substituent, α,β-unsaturated substrates with a weakly acidic proton showed increased rates of ring-opening metathesis mediated by Grubbs-type ruthenium catalysts. 1 H NMR and IR spectral an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The ruthenium-catalyzed AROMP of low-strain cyclic olefins and bicylo[4.2.0]octenes has been investigated extensively and has been championed for producing copolymers that can display a variety of functional groups, controlled backbone sequences, and tunable material properties such as hydrophilicity and glass transition temperatures. [7][8][9][10][28][29][30] To prepare the [4. The purities of the acetylated polymers were confirmed by 1 H-NMR and 13 C-NMR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…The ruthenium-catalyzed AROMP of low-strain cyclic olefins and bicylo[4.2.0]octenes has been investigated extensively and has been championed for producing copolymers that can display a variety of functional groups, controlled backbone sequences, and tunable material properties such as hydrophilicity and glass transition temperatures. [7][8][9][10][28][29][30] To prepare the [4. The purities of the acetylated polymers were confirmed by 1 H-NMR and 13 C-NMR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…The ruthenium-catalyzed AROMP of low-strain cyclic olefins and bicylo[4.2.0]octenes has been investigated extensively and has been championed for producing copolymers that can display a variety of functional groups, controlled backbone sequences, and tunable material properties such as hydrophilicity and glass transition temperatures. , To prepare the [4.2.0] glycopolymers, 4,7-dihydro-1,3-dioxepin or cyclohexene (B monomer) was allowed to react with bicyclo[4.2.0]oct-6-ene-7-carboxamide bearing mannose or fucose (A monomer) in the presence of Grubbs’ third generation catalyst 4 (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of sugar moieties on bicyclo[4.2.0]oct-6-ene-7-carboxamide seemed to significantly lower the reactivity of the reaction, most likely due to steric hindrance as suggested by previous studies. 30,31 Despite allowing the reaction to run for longer than 20 h, copolymers significantly longer than 50 AB units could not be achieved. We have previously demonstrated that polynorbornene 100-mers displaying mannose and fucose efficiently induce AE in mouse sperm 23−25 and polynorbornene 50-mers display the same number of ligands as the [4.2.0] glycopolymers.…”
Section: Design and Preparation Of [420] Glycopolymersmentioning
confidence: 99%
“…However, when bicyclo[4.2.0]­oct-6-ene-7-carboxamide reacts with the ruthenium benzylidene complex (Chart ), it generates Ru-cyclohexylidene carbene (Figure ). , Although not an α-carbonyl containing carbene, the Ru-cyclohexylidene can react with cyclohexene in the presence of additional bicyclo[4.2.0]­oct-6-ene-7-carboxamide monomers to form a linear-alternating copolymer. To this end, we employed bicyclo[4.2.0]­oct-6-ene-7-carboxamide systems in extensive studies because of their fast ROM reactivities compared with previous bicyclo[4.2.0] systems …”
mentioning
confidence: 99%